Código urbano contextualizado: um futuro para o projeto arquitetônico residencial multifamiliar na cidade do Rio de Janeiro - Costa, Bruno Luis de Carvalho da (2018)
This thesis analyzes multifamily residential buildings in the city of Rio de Janeiro, with regard to urban building standards and architects' design practices, observing the production of a built environment that establishes physical and spatial relationships with its immediate surroundings (understood as urban context) or not. It is based on the hypothesis that it is possible to elaborate a legal and planning instrument that allows a flexible interpretation of its demands in order to promote contextualized architectural and urban designs, in which there is a connection between the project practice, the lot, the building and the city. The main objective is to broaden the debate about the role of normative production and the architect in the production of multifamily residential buildings and to establish new bases for discussion on the future of the production of urban norms for the city of Rio de Janeiro through the proposition of a new form of urban code, based on what we call Contextualized Urbanism: the Contextualized Urban Code (CUC). Adopting the microscale of the lot as a parameter, the main urban norms of Rio de Janeiro were analyzed from the beginning of the 20th century under the optics of (de)valuation of the contextualization of buildings and their translation on the urban morphology and on the production of multifamily residences (through analysis of 36 developments and eight architectural and urban designs in the city). For the elaboration of the CUC, we also analyzed reference cases that contribute to the promotion of contextualized developments and to the valorization of the architecture design. It can be concluded that the CUC is relevant in the sense of expanding the possibilities of producing multifamily residential buildings that promote a higher quality of urban life and that advance towards the recognition of environmental and built pre-existences and promote the harmonization of urban morphology while valuing the use of public space.